Physical fitness of elite youth sports climbers: Gender differences and correlates of climbing ability - Němá Kristína; Gilić Barbara; Vrdoljak Dario; Kozák Tomáš; Berta Patrik; Kováč Milan (Biomedical Human Kinetics)
Study aim: This study assessed gender-based differences in physical fitness and the relationships between fitness variables and climbing performance among elite youth sports climbers.